A 13C NMR study of the interactions of Ag13CN and Ag(CN)2– with thiomalic acid, L-methionine and DL-selenomethionine. Issue 5 (2005) - Isab Isab, Anvarhusein A. Anvarhusein A.; Wazeer Wazeer, Mohamed I. M. Mohamed I. M.
Abstract : Complexation of Ag + as AgNO3, solid AgCN and Ag(CN)2 – by labeled and unlabeled L-methionine, DL-selenomethionine and d, l-thiomalate were studied by nuclear magnetic resonance methods. The 13 C NMR indicates that only Ag + react with the both L-methionine, DL-selenomethionine at neutral and higher pH via CO2 – and S or Se atom forming a chelate. The Ag(CN)2 – and AgCN do not bind to either of these two ligands at any pH. The Ag 13 CN, which is an insoluble polymer, can react with thiomalate to form chelate complexes at neutral pH. Various structures for the chelate formations are proposed.